If this book exists, you're in the wrong universe : a novel - Pargin, Jason, 1975- (John dies at the end, 2022)
"New York Times bestselling author Jason Pargin's hilarious and horrifying John Dies at the End series continues with If This Book Exists, You're in the Wrong Universe. If the broken neon signs, shuttered storefronts, and sub-standard housing didn't tip you off, you've just wandered into the city of "Undisclosed". You don't want to be caught dead here, because odds are you just might find yourself rising from the grave. That hasn't stopped tourists from visiting to check out the unusual phenomena that hangs around our town like radioactive fallout. Interdimensional parasites feeding on human hosts, paranormal cults worshipping demonic entities, vengeful teenage sorcerers, we've got it all. Did I mention the possessed toy? It's a plastic football-sized egg that's supposed to hatch an adorable, colorful stuffed bird when a child "feeds" it through a synchronized smartphone app. What's actually inside is an otherworldly monstrosity that's enticing impressionable wayward youth into murdering folks and depositing their body parts inside the egg as if it's a hungry piggy bank to trigger the end of the world. That's where Dave, John, and Amy come in. They face supernatural threats so the rest of us don't have to-and sometimes even earn a couple of bucks to so do. But between the bloody ritual sacrifices and soul-crushing nightmares, our trio realizes this apocalypse is way above their pay grade"--